HUBUNGAN KEKUATAN OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN SERVIS ATAS BOLA VOLI PADA TEAM BOLA VOLI PUTRA HANDAYANI FC TANAH PUTIH ROKAN HILIR - Hafitri Hafitri; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is the correlational. In this study a sample of the entire population sample totaling 12 person Men’s Volleyball Team of handayani fc tanah putih rokan hilir. The instrument of this study tests the strength of arm and shoulder muscles using (Hand Dynamometer) and test services over volleyball. Data were analyzed using product moment.Furthermore, to determine the extent to which the relationship between the strength of the relationship with the arm and shoulder muscles serviceability over the volleyball team volleyball Men’s handayani fc tanah putih rokan hilir,a significant test α = 0.05. Normality test variable X, L0max (0,162) < Ltabel (0.242), and variable normality test Y, L0max (0,1152) < Ltabel (0.242) normal data and research conclusion indicates: there is a,relationship between the strength of the relationship with the arm and shoulder muscles serviceability over the volleyball team volleyball Men’s handayani fc tanah putih rokan hilir with a correlation r = 0.798 where rcount> rtable or 0,798 > 0,602. And relationship is categorized as strong. Thus, Ha is accepted.Key Words: Arm And Shoulder Muscle Strength, Service Above Volleyball